STOCK SPLIT: PENGUJIAN TERHADAP SIGNALING DAN TRADING RANGE PADA BURSA EFEK JAKARTA - Tanjung, Abdul Hafiz (UI Scholars Hub, 2007)
This research was conducted to examine signaling hypothesis and trading range hypothesis for companies splitting their stock in Jakarta Stock Exchange for the period of2000 - 2003. Two statistical analysis were used in this research, parametric statistic i.e. independent t test, paired t test, and the non parametric statistic i.e. Mann-Whitney U test. Normality and equality of variance were done to determine which analysis to be used. Sample size of this research consists of 28 companies which split their stocks and 60 companies which do not split their stocks. Sample was chosen by simple random sampling. The result of this research shows that there is a signaling on profit growth differences in the year 2001, and there is no signaling on yearly profit increase over 4 years before stock splits. On the other hand, there is a trading range on market stock price in the year 2000 and 2003; this was also shown by trading volume stock.